1994
DOI: 10.1056/nejm199402243300807
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Probability of Survival on Patients' Preferences Regarding Cardiopulmonary Resuscitation

Abstract: Older patients readily understand prognostic information, which influences their preferences with respect to CPR. Most do not want to undergo CPR once a clinician explains the probability of survival after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
265
1
10

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(288 citation statements)
references
References 43 publications
8
265
1
10
Order By: Relevance
“…Efforts to resolve disagreements should therefore include exploration of differences in perception. Only a tiny minority of patients would request resuscitation if they understood their prognosis to be very poor 16 , and others have suggested effective ways to discuss prognosis 19 . Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to resolve disagreements should therefore include exploration of differences in perception. Only a tiny minority of patients would request resuscitation if they understood their prognosis to be very poor 16 , and others have suggested effective ways to discuss prognosis 19 . Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…24 There is conflicting evidence regarding patients' treatment preferences at the end of life. Fried et al reported that the burden of treatment, its outcomes and the likelihood of its outcomes all influenced the treatment preferences of older patients who were seriously ill. 25 Unrealistically optimistic expectations of the outcomes of treatment can also lead patients to request interventions, such as cardiopulmonary resuscitation (CPR), that doctors believe are inappropriate. Patients' choices are influenced by the provision of accurate information regarding the outcomes of treatment; one study demonstrated that patients were far less likely to request CPR when they were made aware of the low probability of a successful outcome.…”
Section: Planning Of End-of-life Carementioning
confidence: 99%
“…When given accurate information, many patients who have expressed a desire for CPR change their minds. 1,2 Patients and families often believe that a DNR order means the medical team is giving up on them. This belief is an important and understandable factor in the A.S. case.…”
Section: Lesson 1 -The Need For Educationmentioning
confidence: 99%